Cloning of Phenylalanine ammonia-lyase (PAL) gene fragment from Aquilaria malaccensis Lam. (karas). - Mohamed, Rozi; Wong, M. T. (Forestry Department Peninsular Malaysia, 2009)
Current practice of indiscriminate and illegal felling of 'karas' trees (Aquilaria malaccensis) to extract 'gaharu' in the wild have caused the population to dwindle drastically. 'Gaharu' formed as a result of natural defense mechanism in trees, which unfortunately happens over a long period of time. To better understand natural processes of gaharu-making, we sought to study the roles of defense genes in 'karas' by cloning a gene that synthesizes secondary compounds. The phenylalanine ammonia-lyase (PAL) gene encodes an enzyme in the metabolism of phenylpropanoid compounds, which are produced in response to stress, such as damage by wounding and pathogen attack. We report a cloned PAL gene fragment from A. malaccensis using the polymerase chain reaction (PCR) technique. The fragment was amplified from genomic DNA of a wounded 2-year old tree and cloned into the pGEM-T Easy Vector. The cloned fragment had a length of 610bp and an uninterrupted open reading frame of 201 amino acids. When searched against the Genebank database using BLAST tools, the cloned fragment shared 92% sequence similarity at amino acid level to known PAL proteins. This work will serve as a foundation in identifying important genes for triggering 'gaharu' synthesis.